American wind music : its origin and the instrumental tutors - Kolman, Barry, 1951- (Cambridge Scholars Publishing, 2018)
The transitions that occurred in everyday life after the new "America" was created after the Revolutionary War are reflected in the type of wind music local amateur groups were performing. New composers began writing original works, always trying to wean themselves from the British musical traditions so imbedded in daily life. Selected works of Joseph Herrick, Oliver Shaw, Timothy Olmsted, William Whiteley, Ezekiel Goodale, and Henry E. Moore are analyzed and explored here. The present volume, which will appeal to music lovers and historians alike, traces the development of these new compositions found in available Instrumental Tutors, as well as the instruments most commonly used.